Analysis of Musculoskeletal Disorders (MSDS) Incidence in Employees at The Ogan Komering Ulu Timur District Health Office : A Cross-sectional Study - Yusi Marlioka; Muhammad Prima Cakra Randana; Nani Sari Murni (School of Health Sciences Al-Ma'arif, 2025)
Musculoskeletal disorders (MSDs) are a collection of symptoms or conditions related to muscle tissue, cartilage, tendons, the nervous system, ligaments, bone structure, and blood vessels. MSDs can cause pain, soreness, numbness, swelling, stiffness, and disrupt sleep quality. A preliminary study conducted by the author using the Nordic Body Map (NBM) method on employees of the Ogan Komering Ulu Timur District Health Office showed that 51.2% of employees experienced mild ergonomic risks and 48.8% experienced moderate ergonomic risks. This study aims to analyze the incidence of Musculoskeletal Disorders (MSDs) in employees at the Ogan Komering Ulu Timur District Health Office in 2025. The design of this study is quantitative with a cross-sectional approach. The sample in this study was the total population, namely all employees at the Health Office of Ogan Komering Ulu Timur Regency totaling 86 respondents. Bivariate analysis using the Chi-square test, and multivariate analysis using multiple logistic regression tests with prediction methods. In this study, of the 86 respondents who were at risk and not at risk of MSDs, the proportions were not much different, namely 42 respondents (48.8%) were at risk of MSDs, and 44 respondents (51.2%) were not at risk of MSDs. Bivariate analysis showed that there were 4 variables related to the incidence of MSDs, namely age (p value 0.000), BMI (p value 0.016), length of service (p value 0.000), and work posture (p value 0.000). The dominant factor related to the incidence of MSDs was work posture (p value 0.014; OR 0.197. It is recommended to carry out administrative controls and prepare standard operating procedures in accordance with ergonomic principles that focus on work posture, optimize work station facilities, maintain a balanced nutritional diet, and exercise regularly.